Let's Start With the End: Bibliodrama in an Italian Death Education Course on Managing Fear of Death, Fantasy-Proneness, and Alexithymia With a Mixed-Method Analysis. (September 2021) - Testoni, Ines; Biancalani, Gianmarco; Ronconi, Lucia; Varani, Silvia
This article presents the results of an experience of death education (DE) course with bibliodrama in Italian high schools, which focused on emotions and existential themes. The research analyzed the inability to recognize or describe one's own emotions (alexithymia), fantasy-proneness, and attitudes toward death in two different groups of students: one who took a course on DE (with 113 students) and another who did not participate in it (with 114 students). The use of a mixed method allowed this study to explore the quantitative results that the students indicated in the questionnaire and the qualitative open answers to the final question about how they had profited from this DE course. The results showed that the course had a positive effect, as the DE group significantly decreased alexithymia and negative attitudes toward death, particularly in fear and avoidance of death, making their representation of death less traumatic.